First Measurements of Biogenic Hydrocarbons in Air in a Tropical Cloudy Forest, Monteverde, Costa Rica - Esquivel-Hernández, Germain (2011)
Measurements of biogenic hydrocarbons in ambient air were carried out during 2008 in a cloud y tropical forest in Monteverde, Costa Rica. Isoprene, α-pinene, β-pinene, 3-carene, d-limonene and γ-terpinene were sampled by adsorption cartridges filled with graphitized carbon and Tenax TA and analyzed by GC-FID. Parallelsamples were collected using 2 liters canisters and analyzed by GC-MS. In situ ozone measurements were done by using a UV absorption instrument. Increasing mixing ratios of isoprene, rel ated to photosynthetic activity and ambient temperature, were observed during the morning and afternoon hours. Maximum isoprene’s mixing ratio reached 30 ppbv in March. An increment in the emissions of mon oterpenes during high humidity periods and after rain events was also observed. Average mixing ratios of monoterpenes were between 0.3 and 3 ppbv. During the dry season (December to April), most abundant hydrocarbons were isoprene and d-limonene, whereas in the rainy season (May to November) isoprene a nd α-pinene were dominant. Hydrocarbons mixing ratios were used to estimate the OH and NO3 densitie s. Average OH density was calculated in (4.87 ± 0.17) × 106 mol/cm3. Average NO3 density was calcul ated in (1.39 ± 0.09) × 108 mol/cm3. Average O3 mixing ratio was 30.9 ppbv.